TECHNOLOGY LITERACY AND LEARNING ENVIRONMENT AS PREDICTORS OF STUDENTS' ACADEMIC ACHIEVEMENT: THE MEDIATING ROLE OF AI UTILIZATION - Gunawan, Guntur; Yumiarty, Yuyun (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to analyze the effects of Technology Literacy and Learning Environment on Academic Achievement, with AI Utilization serving as a mediating variable among PGMI students at IAIN Curup. The research employed a quantitative approach using an explanatory design and a survey method. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 4) to examine direct, indirect, and mediating relationships among variables. The results revealed that Technology Literacy had a positive and significant effect on Academic Achievement (β = 0.133; p = 0.032), while Learning Environment demonstrated a stronger positive effect (β = 0.468; p = 0.000). Furthermore, AI Utilization significantly mediated the relationship between Technology Literacy and Academic Achievement (β = 0.182; p = 0.000), as well as the relationship between Learning Environment and Academic Achievement (β = 0.119; p = 0.001). The model showed substantial explanatory power, with R² values of 0.741 for Academic Achievement and 0.711 for AI Utilization. These findings indicate that academic success in higher education is influenced not only by students’ technological competence and supportive learning environments but also by their ability to utilize AI effectively in learning activities. The novelty of this study lies in positioning AI Utilization as a central mechanism linking individual and environmental factors to academic outcomes within teacher education. Practically, the findings suggest that universities should strengthen digital literacy, improve technology-supported learning environments, and promote responsible AI integration. Such efforts can enhance academic performance and prepare future educators for educational ecosystems.